2013
DOI: 10.1016/j.aap.2013.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Updating outdated predictive accident models

Abstract: Reliable predictive accident models (PAMs) are essential to design and maintain safe road networks however, ongoing changes in road and vehicle design coupled with road safety initiatives, mean that these models can quickly become dated. Unfortunately, because the fitting of sophisticated PAMs including a wide range of explanatory variables is not a trivial task, available models tend to be based on data collected many years ago and seem unlikely to give reliable estimates of current accidents. Large, expensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although increasing model complexity may provide better insight into modeled safety performance, additional predictors have often been nonbeneficial. For example, studies of UK single carriageways (undivided two-lane roads) from the 1990s found that only a small fraction of explanatory variables significantly improved the model fit (7); a recent follow-up study confirmed that the best-fitting models did not include any of geometric features (8). Similar conclusions were reached by Finnish researchers in the 1990s (9) and dictated the use of simple models since then (10).…”
mentioning
confidence: 88%
“…Although increasing model complexity may provide better insight into modeled safety performance, additional predictors have often been nonbeneficial. For example, studies of UK single carriageways (undivided two-lane roads) from the 1990s found that only a small fraction of explanatory variables significantly improved the model fit (7); a recent follow-up study confirmed that the best-fitting models did not include any of geometric features (8). Similar conclusions were reached by Finnish researchers in the 1990s (9) and dictated the use of simple models since then (10).…”
mentioning
confidence: 88%
“…Furthermore, problems can be expected with regard to the research database. High-quality data in large quantities for road characteristics, traffic flow, and crashes are rarely readily available and compatibility issues arise when combining different datasets of road characteristics and traffic flow [53]. Yannis et al 2010 [54] improved multilevel negative binomial models to inquire into the effects of the strength of the police enforcement on the number of road accidents during 1998-2002 at the regional level in Greece.Nikiforos et al 2010 [55] aimed at evolving crash prediction models and Accident Modification Factors (AMF) for multilane roads particularly lane widths, type, median width, and shoulder width.…”
Section: Crash Prediction Modelsmentioning
confidence: 99%
“…Schwemer, 2000), road safety (e.g. Wood et al, 2013) and ionospheric physics (e.g. Dorrian et al, 2019).…”
Section: Overview Of Methodsmentioning
confidence: 99%